(untitled) (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: Brucellosis is an endemic zoonotic infection in Saudi Arabia, including Jazan Province, and epidemiological reports about this disease are limited. In this study, we aimed to investigate knowledge, attitudes, and practices regarding brucellosis among the general population of Jazan Province, southwestern Saudi Arabia. Materials and Methods: This is a cross-sectional study conducted using a pretested questionnaire that assessed the level of knowledge, attitudes, and practices toward Brucellosis. The calculated sample size was 384, and 1,055 participants were included representing various genders, ages, and levels of education. Data were collected between March and April 2022 and analyzed using descriptive, chi-square, and t-test analyses. Results: Only 50% of the included participants have heard about Brucellosis. Among those who had heard about Brucellosis, 70% had a good knowledge about Brucellosis and that was significantly associated with male gender, being healthcare workers (HCWs), and having a higher level of education. Participants who directly involved in animal care represented 9%, and attitudes and practices regarding brucellosis were varied from average to unsatisfactory. This variation was significantly affected by the level of knowledge. Conclusion: About 50% of the general population of Jazan Province had never heard about Brucellosis, in a region found prevalent for this disease. Good knowledge was recorded in 70% of those who were aware of Brucellosis, which was significantly associated with the male sex, job as being HCW, and having a higher level of education. These results necessitate public awareness campaign activities to improve knowledge and practices, especially among women, the younger generation, and individuals with limited educational backgrounds. This action could reduce the burden of the disease. J. Adv. Vet. Anim. Res., 9(4): 761–769, December 2022 http://doi.org/10.5455/javar.2022.i646